2017
DOI: 10.1080/15592294.2016.1271853
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA methylation and PM2.5 species in a 450K epigenome-wide association study

Abstract: Although there is growing evidence that exposure to ambient particulate matter is associated with global DNA methylation and gene-specific methylation, little is known regarding epigenome-wide changes in DNA methylation in relation to particles and, especially, particle components. Using the Illumina Infinium HumanMethylation450 BeadChip, we examined the relationship between one-year moving averages of PM 2.5 species (Al, Ca, Cu, Fe, K, Na, Ni, S, Si, V, and Zn) and DNA methylation at 484,613 CpG probes in a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 54 publications
1
29
0
1
Order By: Relevance
“…DNA of whole blood samples were collected between 1999 and 2013. As previously described [36,37], we used the QIAamp DNA Blood Kit (Qiagen, CA, USA) to extract DNA from buffy coat, and performed bisulfite conversion with the EZ-96 DNA Methylation Kit (Zymo Research, CA, USA). To minimize batch effects, we randomized chips across plates and randomized samples based on a 2-stage age-stratified algorithm so that age distributed similarly across chips and plates.…”
Section: Methodsmentioning
confidence: 99%
“…DNA of whole blood samples were collected between 1999 and 2013. As previously described [36,37], we used the QIAamp DNA Blood Kit (Qiagen, CA, USA) to extract DNA from buffy coat, and performed bisulfite conversion with the EZ-96 DNA Methylation Kit (Zymo Research, CA, USA). To minimize batch effects, we randomized chips across plates and randomized samples based on a 2-stage age-stratified algorithm so that age distributed similarly across chips and plates.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis was adjusted for confounding effects of age, sex, and disease status. As a consequence, to prevent an increase in Type I errors, Bonferroni correction was used to analyze specific haplogroup differences between the H and J variants . CpG sites were considered significantly differentially methylated if the Bonferroni‐adjusted P value was less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…We observed that the effect of prenatal PM 2.5 exposure on placental mtDNA content was mediated for 54% by mitochondrial 12S RNA methylation and for 27% by mitochondrial D-loop methylation [49]. Although studies on mitochondrial epigenetics are still in its infancy, PM 2.5 exposure may be a potential candidate with important links to mitochondrial epigenetics [107].…”
Section: Interplay Of Oxidative Stress Epigenetics and The Air Pollmentioning
confidence: 99%